2021
DOI: 10.1200/jco.2021.39.6_suppl.268
|View full text |Cite
|
Sign up to set email alerts
|

Peri-operative morbidity and mortality in a modern series of patients treated with cytoreductive nephrectomy (CN) at five centers.

Abstract: 268 Background: For metastatic renal cell cancer (mRCC) patients considering cytoreductive nephrectomy (CN), perioperative morbidity is important to discuss but few contemporary multi-institutional data are available. The objective of this study is to describe factors associated with perioperative outcomes in a modern multi-institutional cohort of patients treated with cytoreductive nephrectomy. Methods: Data for perioperative complications was recorded for patients treated with CN at 5 centers from 2005-2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Population-based studies indicated a rise in the utilization of CN, increasing from 15% in 1998 to 36–38% in 2008–2011 [3]. Despite evidence supporting CN from both cytokine-era studies and contemporary investigations at high-volume centers with a reasonably low complication rate, only approximately one-third of mRCC patients ultimately underwent CN [3,4]. These findings inherently highlight a selective approach in offering CN within the broader mRCC population.…”
Section: Introductionmentioning
confidence: 98%
“…Population-based studies indicated a rise in the utilization of CN, increasing from 15% in 1998 to 36–38% in 2008–2011 [3]. Despite evidence supporting CN from both cytokine-era studies and contemporary investigations at high-volume centers with a reasonably low complication rate, only approximately one-third of mRCC patients ultimately underwent CN [3,4]. These findings inherently highlight a selective approach in offering CN within the broader mRCC population.…”
Section: Introductionmentioning
confidence: 98%
“…Historically, surgeons have used 30‐ or 90‐day complication and mortality data as standard measures to determine success in patient selection. In modern studies from high‐volume centers, patients treated with cytoreductive nephrectomy have perioperative mortality rates of 1% and major complication rates of 10% 6 . Although these short‐term surgical metrics are clearly important, they do not provide clear information about the impact of surgery on intermediate‐ or long‐term outcomes such as overall survival.…”
mentioning
confidence: 99%